Modal Analysis of the Key Components of RV Reducer - Sun Yongsen; Zhou Yanfei; Yang Xiao; Zhang Xiang; Xia Tian (Jixie chuandong)
The transmission accuracy of RV reducer is mainly affected by the precision of the cycloidal drive,and the performance of the whole machine is directly affected by the dynamics state of the cycloidal gear and the pinwheel. Taking the RV-40 E reducer as the research object,and the three-dimensional model of the cycloidal gear and the pinwheel is built. By using the finite element method,modal analysis is conducted to get the natural frequency and vibration mode at each order of the cycloidal gear and the pinwheel in two working conditions. The results show that it is easy to cause the resonance deformation of cycloid gear and pinwheel when the meshing frequency of cycloidal gear is 1 820 Hz. And that the flange part area of the cycloidal gear and the area connecting pinwheel with the skeleton oil seal are more sensitive to produce deformation. Increase the pinwheel flange radius and adding ribs out of the skeleton oil seal can improve the pinwheel natural frequency to avoid resonance. Adding ribs for cycloidal gear can’t avoid the meshing frequency. Replacing the material of cycloidal gear and selecting the GCr15 with greater modulus of elasticity can make the cycloidal gear avoid the meshing frequency and avoid resonance. Modal analysis results of optimized cycloidal gear and pinwheel provide a theoretical basis of the following dynamics analysis of RV reducer.